2007
DOI: 10.1063/1.2815636
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline structures, surface morphology, and ferroelectric response in ultrathin film of vinylidene fluoride and trifluoroethylene copolymer

Abstract: This paper presents crystalline structures, surface morphology, and improved ferroelectric response in ultrathin film of 70 mol % vinylidene fluoride and 30 mol % trifluoroethylene copolymer with 22 nm thickness. Remanent polarization (Pr) of 45 mC∕m2 was obtained at maximum applied voltage of 11 V (500 MV/m) for the ultrathin film annealed at 142 °C. This Pr value is twice as high than that previously reported. We ascribed higher Pr to both smoothness of sample surface and no significant reduction of crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…Polar phases were maximally created at the annealing temperature of 130°C. This coincides with most previous studies reporting that the annealing temperature would be between 120°C and 140°C . Interestingly, this temperature is between the Curie and melting temperatures of P(VDF‐TrFE) 75:25 mol% copolymers (i.e., melting temperature of 150°C, the Curie transition temperature in the cooling process of 57–79°C and the Curie transition temperature in the heating process of 124°C) .…”
Section: Resultssupporting
confidence: 91%
“…Polar phases were maximally created at the annealing temperature of 130°C. This coincides with most previous studies reporting that the annealing temperature would be between 120°C and 140°C . Interestingly, this temperature is between the Curie and melting temperatures of P(VDF‐TrFE) 75:25 mol% copolymers (i.e., melting temperature of 150°C, the Curie transition temperature in the cooling process of 57–79°C and the Curie transition temperature in the heating process of 124°C) .…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, we have already shown that crystallinity of P(VDF-TrFE) (70/30) was not changed down to 22 nm thickness. 18 As the probe chip of AFM is conductive, one can imagine that ferroelectric switching could be measured upon direct probing by an AFM probe chip. We have tried to measure the direct switching using a conductive AFM probe chip attached to the surface of the sample film without assistance of electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, special attention has been paid for achieving ultrathin P(VDF‐TrFE) films with good ferroelectric properties. Spin coating is a commonly used method for preparing the P(VDF‐TrFE) films on inorganic and organic substrates over a large area although several process parameters, such as initial polymer concentration, spin speed and annealing temperature, affect their ferroelectric properties 1–3, 8–10. Recently, spin‐coated films down to 20 nm thickness have been demonstrated with measurable ferroelectric properties for the low voltage operation 9, 10.…”
Section: Summary Of R From Xrd Vc and D33mentioning
confidence: 99%
“…Spin coating is a commonly used method for preparing the P(VDF‐TrFE) films on inorganic and organic substrates over a large area although several process parameters, such as initial polymer concentration, spin speed and annealing temperature, affect their ferroelectric properties 1–3, 8–10. Recently, spin‐coated films down to 20 nm thickness have been demonstrated with measurable ferroelectric properties for the low voltage operation 9, 10. Meantime, piezoresponse force microscopy (PFM) has been developed to investigate the structure and dynamics of ferroelectric domains and to understand polarization related processes in ferroelectric thin films 11, 12.…”
Section: Summary Of R From Xrd Vc and D33mentioning
confidence: 99%